ИНСАНДА КӨРКЕМ-ДӨРЕТИЎШИЛИК УҚЫПЛЫЛЫҚЛАРЫН РАЎАЖЛАНДЫРЫЎДЫҢ ТИЙКАРҒЫ АСПЕКТЛЕРИ - Уразимова, Т.В. (ILIM hám JÁMIYET, 2021)
The article is devoted to the aspects of artistic and creative development of the individual in modern society. This problem of science is one of the most pressing issues of today.